Can God Be Timeless Without Creation and Temporal Subsequent to Creation? : A Reply to Erik J. Wielenberg - Erasmus, Jacob (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2021)
Erik J. Wielenberg argues that William Lane Craig’s understanding of creatio ex nihilo (creation out of nothing) is logically incoherent. According to Craig’s account, God was timeless or atemporal without the universe, but created the universe (including time itself) and entered into time (or became temporal) at the moment of creation. Wielenberg argues, however, that this account entails that (i) the first cause of time is both timeless and temporal at the first moment of time, and (ii) the beginning of time is both caused and uncaused. In this article, I respond to Wielenberg’s objections and show that they are unsuccessful.